Combined’ Neck/Back Pain and Psychological Distress/Morbidity Among the Saudi Population: A Cross-Sectional Study - Al-Ghamdi, Sameer; Shubair, Mamdouh M.; Angawi, Khadijah; Al-Zahrani, Jamaan; Khormi, Abdulrahman Ali M.; Alshammari, Reem Falah; Alshammari, Nawaf Safaq; Aldahash, Raed; Otayf, Bander Yahya; Al-Zahrani, Hayat Saleh; Aleshaiwi, Manayir Sultan; Aldossari, Khaled K. (Frontiers in Psychology, 2022)
Background Psychological distress/morbidity is amongst the primary reason for the cause of pain at multiple sites, its progression, and recovery. Though still not very clear if physical pain in the neck or the back may predict psychological morbidities or not. Thus, we investigated the association between combined neck or back pain and psychological distress/morbidity. Methods A cross-sectional study was conducted in Al-Kharj, Saudi Arabia, including 1,003 individuals. The questionnaire comprised of General Health Questionnaire-12 (GHQ-12) and some questions about neck and back pain. Data analysis was done using statistical software SPSS version 26.0. Results The results of the multivariate analysis revealed a significant positive association between neck/back pain status and total GHQ score (unstandardized Beta = 2.442, P ≤ 0.0001). Having neck/back pain had almost a 2.5 times greater risk of psychological distress/morbidity. Further, females were more likely to have a higher risk of psychological distress/morbidity (unstandardized Beta = 1.334, P = 0.007) than males while adjusting for sociodemographic and clinical characteristics. Conclusion The combination of neck and back pain was significantly associated with the Saudi population’s psychological problems. Therefore, the Saudi government needs to devise high-risk strategies and allocate adequate resources to the cause so that at-risk people can be shielded from the adverse complications arising from this condition in the long run.